Quantitative analysis of fatigue fracture surface in the duplex steel - Sozańska, Maria (Image analysis and stereology, 2002)
We present a quantitative and qualitative analysis of the fatigue surface of Z2CND2205 duplex steel. Both the ferritic and austenitic phases of this duplexsteel are investigated. The observed brittleness of the steel is here due to the presence of hydrogen. The hydrogen influence is complex in that thetwo phases are altered by hydrogen in different ways. Quantitative parameters describing striations spacing in each phase are measured.
Keywords: Jeklo; Materials Testing; Korozija odlitkov; Steel; Materiali, testiranje; Corrosion Casting; Tensile Strength; Raztezanje, trdnost; Slika, obdelava z računalnikom; Image Processing, Computer-Assisted; Rentgenski žarki, lomljenje; X-Ray Diffraction; preiskava materiala; jekla; korozija